Embodied Numeracy Play in Physical Education: Effects on Fundamental Motor Skills and Critical Thinking in Primary School Children - Tiara Juniati Rahmaningrum; Advendi Kristiyandaru; Nanik Indahwati (AL-ISHLAH: Jurnal Pendidikan, 2025)
Physical education (PE) has the potential to support both motor and cognitive development; however, structured integration of numeracy within PE remains underexplored. This study investigated the effects of Embodied Numeracy Play (ENP), a movement-based instructional approach grounded in embodied cognition, on primary school students’ fundamental motor skills (FMS) and critical thinking (CT). A quasi-experimental pretest–posttest design was employed involving 57 third-grade students who participated in either ENP-based PE lessons or conventional PE instruction over a four-week period. FMS were assessed using the Test of Gross Motor Development–Second Edition (TGMD-2), while CT was measured using a validated observational rubric. Data were analyzed using multivariate and univariate analyses. Students in the ENP group demonstrated significantly greater improvements in both outcomes compared with the control group. The intervention produced a large effect on FMS development and a moderate effect on CT. A positive association was also observed between gains in motor skills and critical thinking. The findings indicate that integrating numeracy reasoning into physical play can simultaneously enhance motor competence and higher-order thinking. This study provides empirical support for embodied cognition and highlights the potential of cognitively enriched PE as an integrative learning approach in primary education.